Faktor-Faktor Yang Mempengaruhi Firm Value Pada Perusahaan Manufaktur Di BEI - Aaron Edward Natanael, Rousilita Suhendah (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to determine the effect of profitability, leverage, and firm size on firm value. This research uses secondary data which is financial information from the financial statements and annual report of the company. The research sample used 72 manufacturing companies listed on the Indonesia Stock Exchange during the period 2016-2018. Statistical analysis which is performed using multiple regression analysis to test the hypothesis. The results of this analysis indicate that profitability has negative effect on firm value, while leverage and firm size has no effect on firm value.